Strengthening the right of children to express their views in family law procedures - Wopera, Zsuzsa (European Integration Studies, 2023)
In recent years, significant progress has been made in Hungary in strengthening the right of children to express their views. The study analyzes what amendments have been made in Hungarian civil law and civil procedure law in this field. The study analyzes how to interpret the right of a child who is capable of forming views in the light of the findings of the general comments issued by the UN Committee on the Rights of the Child. In addition, the article analyzes in detail Article 21 of the Brussels IIb regulation on the expression of the child's views and the related rules for refusal of recognition and refusal of enforcement of decisions in matters of parental responsibility. The study provides a detailed ‘practice guide’ for Hungarian legal practice on how to apply the provisions that entered into force in August 2022 consistently with EU law and international legal interpretations. The article provides answers to the procedural questions that arose after the entry into force of the amendment of Hungarian Civil Code in 2022. The author takes a stand on the question of which stage of the civil procedure and with what content it is worth issuing the notice for the child.